Performances Comparison Of EMG Signal Analysis For Manual Lifting Using Spectrogram - Tengku Zawawi , Tengku Nor Shuhada; Abdullah, Abdul Rahim; Shair, Ezreen Farina; Mohamad Saleh, Saleha (Penerbit Universiti, UTeM, 2016)
-